The drop-out phenomenon in John Paul II University in Biała Podlaska – report of research - Dorota Tomczyszyn; Wiesław Romanowicz; Olga Filipiak; Adam Szepeluk (Rozprawy Społeczne)
Abstract Civilization changes, the development of digital technologies, changes in the labor market significantly affect modern education. In higher education in Poland, as well as in the world, the spreading phenomenon of drop-out, understood as the abandonment of the chosen field of study by a student, has been noticed for several years. The purpose of this research was to identify the reasons for drop-outs and a general overview of the unified educational paths of students at the John Paul II University in Biała Podlaska. The article is empirical in nature.